Erasmus + coordinator as a tutor and mentor at higher educational establishments of Ukraine under the conditions of the academic mobility increase - Ivanytska, Oksana (ScienceRise: Pedagogical Education, 2018)
The article analyzes the modern state of higher education in Ukraine, realization of academic mobility, discovers peculiarities of introducing tutoring and mentoring under Ukrainian realities. There was realized the comparative analysis of providing tutor and mentor activity in Ukraine and HEE in Ukraine and Europe. There were separated functions, realized by Erasmus + coordinators for providing tutor and mentor activity in Ukraine. Especially, there was grounded a necessity to introduce tutoring and mentoring in Ukrainian HEE. The key factors that influence a necessity of introducing tutoring and mentoring are: internationalization, increase of academic mobility, problems with refugees, new challenges in higher education and new requirements to providing its quality. The program Erasmus + is for today the most large-scale instrument of academic mobility realization in Europe. Just that is why tutors and mentors help students that study during one semester (credit mobility) or MA course (stage mobility) to realize their potential and to finish their study successfully at a partner HEE. At studying students that realize academic mobility get help from tutors at solving practical tasks, laboratory works. Mentors help to adapt to living conditions, traditions of another country, language. Only complex tutorship provides the harmonic development and success of a student, realizing the principle of student-centered study. A situation as to implementing tutoring and mentoring differs depending on a country. Success of a University today depends also on realization of academic mobility and desire of foreign students to study at one or another HEE. This article separated the main functions, realized by Erasmus + for providing tutor and mentor activity: informational (communication about possibilities of exchange, necessary information), communicative (setting a dialogue between all participants of mobility), organizational (preparation of necessary documentation), educational (instructions as to behavior abroad), psychological (determination of psychological features of each person and individual peculiarities for providing comfort conditions of staying abroad). The article grounds a possibility of introducing tutoring and mentoring at HEE of Ukraine, based on the experience of foreign ones